Case Report: Clinical and Immunological Features of a Chinese Cohort With Mycoplasma-Induced Rash and Mucositis - Liu, Lipin; Wang, Ying; Sun, Jinqiao; Wang, Wenjie; Hou, Jia; Wang, Xiaochuan (Frontiers in Pediatrics, 2020)
Dermatological disorders are the most common extrapulmonary complications of Mycoplasma pneumoniae, of which Mycoplasma-induced rash and mucositis (MIRM) has recently been proposed to be a separate diagnostic entity. MIRM could easily be misdiagnosed as atypical Stevens-Johnson syndrome by clinicians due to the unawareness of this rare disease. We retrospectively reviewed the inpatient database from Jan. 2016 to Dec. 2019 of the Children’s Hospital of Fudan University. In total, 5 patients (mean age 5.5 years, 3 male) matched the diagnostic criteria of MIRM. All patients had scattered lesions and more than 2 sites of mucosal involvement. The serum IgA level of 3 patients was higher than normal. Two patients had a significant decrease in peripheral blood CD3+ T and CD4+ T cells that improved with recovery. The percentage of TCRαβ+ CD4-CD8-T cells of Patient 5 was higher than normal. All patients received treatments with antibiotics and corticosteroids, 3 patients received intravenous immunoglobulin. Dyspigmentation was the most common complication (60%), two patients had a full recovery. MIRM is a separate entity with predominant mucosal involvement and excellent prognosis that more often affects younger patients. Excessive inflammatory reactions may lead to immune disorders, including lymphopenia and a redistribution of CD4+ T cells. We recommend that pneumonia accompanied by mucocutaneous eruptions, especially in young patients, should raise clinical suspicion of MIRM.